Manajemen Pembiayaan Jual Beli & Murabahah Teknik Implementasi Bai’ Al-Murabahah, As-Salam, dan Istishna dalam Pembiayaan Konsumtif dan Produktif - Apriyanto Apriyanto; Dini Selasi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The development of Islamic financial institutions has encouraged the increased use of sale-based financing contracts as an alternative financing system in accordance with Islamic principles. This study aims to analyze the management of sale-based financing and the implementation techniques of bai' al-murabahah, as-salam, and istishna' contracts in both consumer and productive financing. The method used in this study is a qualitative descriptive method through a literature review by reviewing various literature related to Islamic financing. The results show that murabahah financing is more widely used to meet consumer needs because it provides price certainty and profit margins. Meanwhile, as-salam and istishna' contracts are more widely applied in productive sectors such as agriculture, trade, and the manufacturing industry. The implementation of good financing management includes the planning stage, feasibility analysis, contract implementation, supervision, and resolution of problematic financing. With proper management, sale-based financing can improve community welfare and support the development of the Islamic economy..